The impact of internal audit independence on internal audit effectiveness: A case study of Vietnam - Lam, Nguyen Thi Hong; Ha, Vu Thuy; Thuy, Pham Thi Thu (Edelweiss Applied Science and Technology, 2025)
Internal audit is a crucial instrument for achieving efficient business oversight and adding value. Assessing key factors influencing its effectiveness, including independence, is therefore paramount for organizations aiming to maximize the internal audit's contribution. This study investigates the impact of internal audit independence on internal audit effectiveness. Drawing on primary data, a survey was administered to 265 internal auditors and managers working in corporations with established internal audit functions across Vietnam. Descriptive statistics, including a frequency table, mean, and standard deviation, provided preliminary insights, while inferential statistics, including Pearson’s correlation analysis and regression analysis, utilizing SPSS 22, were employed to test the hypothesized relationship. The empirical findings demonstrate a robust and statistically significant positive influence of internal audit independence on the perceived effectiveness of internal audit activities. These results conclusively highlight independence as a critical determinant of internal audit effectiveness (β = 0.569, p-value = 0.000). Based on this evidence, the study provides actionable recommendations aimed at internal audit departments, senior management, and relevant regulatory bodies in Vietnam to strengthen internal audit independence and enhance their overall contribution to organizational governance.